Flexural Performance of Composite RC Beams Having an ECC Layer at the Tension Face - Khan, Sajjad Wali; Ali, Yousaf; Khan, Fasih Ahmed; Fahim, Muhammad; Gul, Akhtar; Ullah, Qazi Sami; ul-Islam, Shams- (Periodica Polytechnica Civil Engineering, 2023)
This paper presents an experimental study on the flexural behavior of composite Reinforced Concrete (RC) beams having a monolithic Engineered Cementitious Composites (ECC) layer at the tension face. Due to the brittle nature of normal concrete, clear cover on the tension side of beam cracks results in spalling and corrosion of reinforcement. The proposed technique overcomes the inherent brittle behavior of normal concrete with the incorporation of ECC on the tension face. This also helps in reducing bond-splitting, cover-spalling, and buckling of reinforcement in RC flexural members. For testing purposes, six full-scale beam specimens (225 mm x 300 mm x 2400 mm) with the same reinforcement were cast and tested. Out of six, two specimens were made of conventional concrete, whereas the remaining four (two each) had an ECC layer of 75mm and 100mm thick at the tension face respectively. Each specimen was installed with three strain gauges (one each at the midspan top & bottom surface of concrete and one midspan rebar on the tension face) and one LVDT at midspan. The samples were then subjected to simple monotonic loading under a third-point bending test as per ASTM C78. The load-displacement, stress-strain and moment-curvature curves were obtained for all the tested specimens. It was found that ECC-strengthened beam samples displayed an increased flexural performance at first crack, yield, and ultimate load-carrying capacity as compared to conventional RC specimens. Whereas a better crack arrest with even distribution of cracks and improvement in ductility was observed for the ECC-strengthened composite beams.